Effect of moderate dosage of chlorpropamide in pregnancy on fetal outcome. Issue 4 (April 1974) - Sutherland, H. W.; Bewsher, P. D.; Cormack, J. D.; Hughes, C. R. T.; Reid, Anne; Russell, G.; Stowers, J. M.
Abstract : The outcome of 19 pregnancies is reviewed in women receiving daily doses of at least 200 mg chlorpropamide for varying degrees of glucose intolerance. 4 required insulin in late pregnancy. In 13 mothers who had chlorpropamide during the first 13 weeks of pregnancy no fetal abnormality occurred. There were 2 intrauterine deaths, 1 neonatal death, 6 babies with birthweights greater than the 90th centile, and 2 with birthweights below the 10th centile. The total dosage taken during pregnancy varied from 5 to 105 g and the duration of administration varied from 3 to 39 weeks. Though the severity of diabetes loosely correlated with the daily chlorpropamide dosage, no constant relation existed between high daily dosage of chlorpropamide and obstetric or neonatal complications. It is concluded that it is more likely to be the poor control of the maternal diabetes in pregnancy than a pharmacological effect of the chlorpropamide on the fetal pancreas which is responsible for the poor results reported. 6 infants had intravenous glucose tolerance tests done within 3 hours of birth and the rate of glucose disposal and insulin response was found to be greater than in infants of untreated mothers with less severe diabetes.